Timing, frequency, and duration of incubation recesses in dabbling ducks - Croston, Rebecca (Ecol Evol, 2020)
Nest attendance is an important determinant of avian reproductive success, and identifying factors that influence the frequency and duration of incubation recesses furthers our understanding of how incubating birds balance their needs with those of their offspring. We characterized the frequency and timing (start time, end time, and duration) of incubation recesses for mallard (Anas platyrhynchos) and gadwall (Mareca strepera) hens breeding in Suisun Marsh, California, USA, and examined the influences of day of year, ambient temperature at the nest, incubation day, and clutch size on recess frequency and timing using linear mixed models. Mallard, on average, took more recesses per day (1.69 ± 0.80, mean ± standard deviation) than did gadwall (1.39 ± 0.69), and 45% of mallard nest‐days were characterized by two recesses, while only 27% of gadwall nest‐days were characterized by two recesses. Mallard morning recesses started at 06:14 ± 02:46 and lasted 106.11 ± 2.01 min, whereas mallard afternoon recesses started at 16:39 ± 02:11 and lasted 155.39 ± 1.99 min. Gadwall morning recesses started at 06:30 ± 02:46 and lasted 91.28 ± 2.32 min, and gadwall afternoon recesses started at 16:31 ± 01:57 and lasted 192.69 ± 1.89 min. Mallard and gadwall started recesses earlier in the day with increasing ambient temperature, but later in the day as the season progressed. Recess duration decreased as the season progressed and as clutch size increased, and increased with ambient temperature at the nest. The impending darkness of sunset appeared to be a strong cue for ending a recess and returning to the nest, because hens returned to their nests earlier than expected when recesses were expected to end after sunset. Within hens, the timing of incubation recesses was repeatable across incubation days and was most repeatable for mallard afternoon recesses and on days in which hens took only one recess. Hens were most likely to be away from nests between 04:00 and 07:00 and between 16:00 and 19:00; therefore, investigators should search for nests between 07:00 and 16:00. Our analyses identified important factors influencing incubation recess timing in dabbling ducks and have important implications for nest monitoring programs.